O papel da ONU na construção dos direitos humanos - Bezerra Neto, Bianor Arruda (2011)
The value of culture as a primordial element, which is conditioned by the worldview of the people who build it. The idea that every cultural product has its relevance attested in the sense that life has in every worldview, which is always part of a launching point that gives it meaning, hypothetical, mythical, while totally based on hard facts. The value as a basis for ethical norms, moral norms, legal rules. Human rights as an expression of ethics founded on human dignity. The human rights law as a branch of law whose phenomenology is conducted internationally. The UN as a cultural product of an Era, founded on truth contained in the worldview of those who created it. The UN as an institution that synthesizes values of various cultural expressions of the planet, a catalyst for awareness on human rights, promoting the creation of official human rights law.